The Intestinal Redox System and Its Significance in Chemotherapy-Induced Intestinal Mucositis. (9th May 2022) - Yu, Qing-Qing; Zhang, Heng; Guo, Yujin; Han, Baoqin; Jiang, Pei
Abstract : Chemotherapy-induced intestinal mucositis (CIM) is a significant dose-limiting adverse reaction brought on by the cancer treatment. Multiple studies reported that reactive oxygen species (ROS) is rapidly produced during the initial stages of chemotherapy, when the drugs elicit direct damage to intestinal mucosal cells, which, in turn, results in necrosis, mitochondrial dysfunction, and ROS production. However, the mechanism behind the intestinal redox system-based induction of intestinal mucosal injury and necrosis of CIM is still undetermined. In this article, we summarized relevant information regarding the intestinal redox system, including the composition and regulation of redox enzymes, ROS generation, and its regulation in the intestine. We innovatively proposed the intestinal redox "Tai Chi" theory and revealed its significance in the pathogenesis of CIM. We also conducted an extensive review of the English language-based literatures involving oxidative stress (OS) and its involvement in the pathological mechanisms of CIM. From the date of inception till July 31, 2021, 51 related articles were selected. Based on our analysis of these articles, only five chemotherapeutic drugs, namely, MTX, 5-FU, cisplatin, CPT-11, and oxaliplatin were shown to trigger the ROS-based pathological mechanisms of CIM. We also discussed the redox system-mediated modulation of CIM pathogenesis via elaboration of the relationship between chemotherapeutic drugs and the redox system. It is our belief that this overview of the intestinal redox system and its role in CIM pathogenesis will greatly enhance research direction and improve CIM management in the future.